Answer:
The nth term of the given sequence tₙ = 3 n - 7
Step-by-step explanation:
Given sequence - 4 , -1 , 2 , 5, 8 , .....
First term a = -4
The difference of two terms of a given sequence
d = -1 - (-4) = -1 +4 = 3
d = 2 - (-1) = 2 +1 = 3
d = 5 -2 = 3
d = 8 - 5 =3
The difference of two terms of a given sequence is equal
∴ The given sequence is in Arithmetic progression(AP)
The nth term of given sequence
[tex]t _{n} = a + ( n-1 ) d[/tex]
[tex]= -4 + (n -1 ) 3 \\= - 4 + 3n - 3 \\= 3 n - 7[/tex]
Final answer:-
The nth term of the given sequence tₙ = 3 n - 7